Effects of Immune Stress on Performance Parameters, Intestinal Enzyme Activity and mRNA Expression of Intestinal Transporters in Broiler Chickens - Y. Feng; X. J. Yang; Y. B. Wang; W. L. Li; Y. Liu; R. Q. Yin; J. H. Yao (Asian-Australasian Journal of Animal Sciences, 2012)
Immune stress is the loss of immune homeostasis caused by external forces. The purpose of this experiment was to investigate the effects of immune stress on the growth performance, small intestinal enzymes and peristalsis rate, and mRNA expression of nutrient transporters in broiler chickens. Four hundred and thirty-two 1-d-old broilers (Cobb500) were randomly assigned to four groups for treatment; each group included nine cages with 12 birds per cage. Group 1 = no vaccine (NV); Group 2 = conventional vaccine (CV); group 3 = lipopolysaccharide (LPS)+conventional vaccine (LPS); group 4 = cyclophosphamide (CYP)+conventional vaccine (CYP). The results demonstrated that immune stress by LPS and CYP reduced body weight gain (BWG), feed intake (FI), small intestine peristalsis rate and sIgA content in small intestinal digesta (p<0.05). However, the feed conversion ratio (FCR) remained unchanged during the feeding period. LPS and CYP increased intestinal enzyme activity, relative expression of SGLT-1, CaBP-D28k and L-FABP mRNAs (p<0.05). LPS and CYP injection had a negative effect on the growth performance of healthy broiler chickens. The present study demonstrated that NV and CV could improve growth performance while enzyme activity in small intestine and relative expression of nutrient transporter mRNA of NV and CV were decreased in the conditions of a controlled rational feeding environment. It is generally recommended that broilers only need to be vaccinated for the diseases to which they might be exposed.